2023
DOI: 10.1111/jop.13396
|View full text |Cite
|
Sign up to set email alerts
|

Association between autoimmune rheumatic diseases and head and neck cancer: Systematic review and meta‐analysis

Abstract: Background: Personal history of autoimmune rheumatic diseases has been implicated in the development of malignant neoplasms. Our aim was to assess the risk of head and neck (H&N) cancers in patients with autoimmune rheumatic diseases. Methods:The articles search included PubMed, EMBASE, LILACS, The Cochrane Library, CINAHL, Scopus, Web of Science, and Google Scholar with no language restrictions for studies published from inception of the databases to August 20, 2022, assessing the risk of H&N cancer in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Thus, large-scale studies could provide an excellent opportunity to gain insight into the intricate relationship between autoimmune conditions and cancer development. Notably, a recent systematic review and meta-analysis revealed a 2.35-fold increase in the overall incidence of HNC among individuals with autoimmune rheumatic diseases, surpassing the rates observed in the general population [ 13 ]. Moreover, the present study identified a significant 1.49-fold increase in the overall incidence of RA events among patients with HNC compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, large-scale studies could provide an excellent opportunity to gain insight into the intricate relationship between autoimmune conditions and cancer development. Notably, a recent systematic review and meta-analysis revealed a 2.35-fold increase in the overall incidence of HNC among individuals with autoimmune rheumatic diseases, surpassing the rates observed in the general population [ 13 ]. Moreover, the present study identified a significant 1.49-fold increase in the overall incidence of RA events among patients with HNC compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HNC has exhibited associations with various autoimmune rheumatic diseases [ 10 , 11 , 12 ]. Moreover, one recent study showed that individuals with autoimmune rheumatic diseases, inclusive of conditions affecting the thyroid, oral cavity, and nasopharynx, exhibited a conspicuously heightened risk of developing HNC in comparison to the general populace [ 13 ]. One investigation conducted within the European population revealed an augmented susceptibility to HNC among individuals diagnosed with RA [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of the immune system in tumor regulation is particularly evident in the immunocompromised. Iatrogenic solid organ transplant, diabetes, autoimmunity requiring immunosuppressive therapy, HIV and hemoproliferative malignant disease or disorders and aging, are all associated with an increased risk of developing head and neck cancer (HNC) and worse outcomes [1][2][3][4][5][6][7][8][9][10][11]. Proliferating tumors utilize many forms of immunosuppression to tip the balance of immunoediting toward tumor progression [12].…”
Section: Introductionmentioning
confidence: 99%